Fully screen‐printed silicon solar cells with local Al‐p+ and n‐type POLO interdigitated back contacts with a VOC of 716 mV and an efficiency of 23%. (4th March 2021) - Haase, Felix; Min, Byungsul; Hollemann, Christina; Krügener, Jan; Brendel, Rolf; Peibst, Robby
Abstract: We demonstrate the fabrication of a fully screen‐printed p‐type silicon solar cell with local hole‐collecting Al‐alloyed (Al‐p + ) contacts with a record open circuit voltage of 716 mV. The solar cell is fabricated by using almost the same process equipment as PERC cells. One of the dominant recombination losses in PERC cells is the recombination in the passivated and in the contacted emitter regions that so far limit the open circuit voltage to values below 700 mV. We eliminate these loss channels by substituting the P‐diffused emitter by a passivating n‐type poly‐Silicon on Oxide (nPOLO) contact. We place this contact on the rear side because of its otherwise strong parasitic absorption. The Al‐p + contacts are also located at the rear side to avoid front‐side shading. This results in a POLO‐IBC cell structure. The efficiency of the best cell so far is 23.0% with a designated area of 4 cm 2 fabricated on a M2‐sized wafer. Scanning electron microscopy reveals an Al‐p + thickness of less than 3.3 μm and only a few 100 nm at the contact ends, which is less than the 5 μm typically for optimized Al‐p + contacts. A comparison of measured and simulated current‐voltage curves over a variation of the contact fraction extracts a high saturation current density of the Al‐p + contact of J 0‐Al ‐p+ = 2, 250 fA cm −2 for the current screen‐print conditions and Al‐paste causing an absolute efficiency loss of 0.5%abs . The recombination at the AlOx /SiNy surface and the shunt resistance limits the cell by 0.6%abs each. Abstract : We demonstrate the fabrication of a fully screen‐printed p‐type silicon solar cell with local hole‐collecting Al‐alloyed Al‐p+ contacts. Printing the Ag finger grid between the Al‐fingers both with an finger pitch of 1 mm and finger heights of 25 μm requires optimization of the printing parameters of both printing processes resulting in non‐interrupted Al and Ag fingers with a homogeneous cross‐section. We gain a POLO‐IBC cell efficiency of 23% and an open‐circuit voltage of 716 mV.